The effect of early mobilization on constipation after abdominal surgery: A systematic review: The effect mobilization on constipation - Öztaş , İsmail; Yava , Ayla; Koyuncu , Aynur (Journal of Surgery and Medicine, 2024)
Background/Aim: Constipation can occur after abdominal procedures. In this study, we investigated whether early mobilization after abdominal surgery is effective for treating constipation. Methods: We conducted a systematic review of studies implementing early and planned mobilization after abdominal surgical procedures. We extracted studies published from 2012–2022 from six electronic databases: PubMed, Google Scholar, Science Direct, Cochrane, TürkMedline, and Ulakbim. The data were collected by two reviewers following a pre-designed subtraction form. We made use of narrative synthesis when presenting our results. Results: We examined 10 articles that satisfied the inclusion criteria; patients underwent a cesarean section in four studies, bariatric surgery (gastric bypass) in one study, liver resection in one study, radical cystectomy in two studies, cholecystectomy in one study, and a kidney transplant in one study. The studies were characterized by differences in the early mobilization programs applied to patients after abdominal surgery. In two of the studies, the patients were mobilized accordingly to daily step goals; in five studies only early stimulation and walking attempts were utilized. In three of the studies, the patients were mobilized within the scope of mobilization programs prepared in detail after surgery, and the targets were determined in terms of distance walked. All of the studies stipulated that physical activity should gradually increase over time. Conclusion: Early and planned mobilization programs applied after surgery had positive effects on first gas/first stool output time, the severity of abdominal distension, the occurrence of nausea/vomiting, and the onset of oral intake.